Attitudes of the Students of the University College of Educational Sciences; UNRWA in the West Bank, towards the Teaching Profession form their perspective - Marbou, Sahar Said (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the attitudes of the students of the University College of Educational Sciences; UNRWA in the West Bank, towards the teaching profession. To achieve the objectives of the study, the researcher followed the descriptive survey method, where a questionnaire was designed that consisted of (38) phrases distributed over five fields, which were distributed to a random sample of (165) male and female students in the college. The results of the study showed that the attitudes of the students of the University College of Educational Sciences; UNRWA in the West Bank, towards the teaching profession, obtained an overall average (3.56 out of 5), i.e. a (high) degree. As for the levels achieved within the five domains: Firstly, Attitudes towards preparation for the teaching profession achieved the highest average (3.91). Secondly, the teacher’s personal features achieved an average of (3.84). Thirdly, the future of the teaching profession achieved an average of (3.70). Fourthly, the teaching profession achieved an average of (3.65). All four domains received a “significant degree”. Finally, the social and economic trends of the profession achieved an average of (3.25) and a “medium degree”. It also showed that there are differences in the attitudes of students of the University College of Educational Sciences; UNRWA in the West Bank, towards the teaching profession due to the gender variable. The highest average was for females’ sake, the academic level; the fourth level, and according to the place of residence. In the field of attitudes towards the teaching profession between (the village and the camp), the highest average was for the camp’s sake. Furthermore, in the field of preparation for the teaching profession between (the city and the village), the highest score was for the city’s sake. In the field of attitudes towards the future of the teaching profession between (the village and the camp), the highest score was attained by the camp. It also showed that there were no statistically significant differences in the trends of the sample due to the cumulative average variable, with the exception of the field of attitudes towards the teaching profession between (less than 70- and more than 85) and in favor of (more than 85). In light of the results, the researcher presented a set of recommendations and suggestions.